Building the Future of Early Childhood: Optimizing Basic Services through the Holistic Integrative Early Childhood Development Model - Aip Saripudin; Herman Beni (Universitas Islam negeri Mahmud Yunus Batusangkar, 2025)
Holistic Integrative Early Childhood Development is a comprehensive and integrated service aimed at ensuring children possess the necessary abilities and receive their rights as children. This study aims to describe the model of Holistic Integrative Early Childhood Education (HI-ECE) services and the collaborative efforts between ECE institutions and relevant partners. The research adopts a qualitative phenomenological approach and was conducted in West Java Province, involving 50 schools and 12 key informants with experience in managing ECE institutions. Data collection techniques included structured interviews, observations, and documentation. Data analysis followed a qualitative process consisting of data collection, data reduction, data analysis, data display, and drawing conclusions. The results indicate that ECE institutions have made efforts to implement HI-ECE through five types of services: education, parenting, health, protection, and welfare. Partners involved in the development of holistic integrative early childhood programs include community organizations, health units, professional organizations, government agencies, and religious organizations. Therefore, the HI-ECE program needs to be continuously promoted so that children can enjoy their right to learn in a fun, safe, and joyful environment. Collaboration and support from relevant partners must be continuously pursued through programs that prioritize the needs and rights of young children.